High Calcium Bioglass Enhances Differentiation and Survival of Endothelial Progenitor Cells, Inducing Early Vascularization in Critical Size Bone Defects - Eldesoqi, Karam; Seebach, Caroline; Nguyen Ngoc, Christina; Meier, Simon; Nau, Christoph; Schaible, Alexander; Marzi, Ingo; Henrich, Dirk (PLOS ONE, 2013)
Early vascularization is a prerequisite for successful bone healing and endothelial progenitor cells (EPC), seeded on appropriate biomaterials, can improve vascularization. The type of biomaterial influences EPC function with bioglass evoking a vascularizing response. In this study the influence of a composite biomaterial based on polylactic acid (PLA) and either 20 or 40% bioglass, BG20 and BG40, respectively, on the differentiation and survival of EPCs in vitro was investigated. Subsequently, the effect of the composite material on early vascularization in a rat calvarial critical size defect model with or without EPCs was evaluated. Human EPCs were cultured with β-TCP, PLA, BG20 or BG40, and seeding efficacy, cell viability, cell morphology and apoptosis were analysed in vitro. BG40 released the most calcium, and improved endothelial differentiation and vitality best. This effect was mimicked by adding an equivalent amount of calcium to the medium and was diminished in the presence of the calcium chelator, EGTA. To analyze the effect of BG40 and EPCs in vivo, a 6-mm diameter critical size calvarial defect was created in rats (n = 12). Controls (n = 6) received BG40 and the treatment group (n = 6) received BG40 seeded with 5×105 rat EPCs. Vascularization after 1 week was significantly improved when EPCs were seeded onto BG40, compared to implanting BG40 alone. This indicates that Ca2+ release improves EPC differentiation and is useful for enhanced early vascularization in critical size bone defects.